Capacidade funcional de idosos institucionalizados com e sem doença de Alzheimer - Ferreira, Lucas Lima [UNESP]; Cochito, Tais Cristina; Caíres, Flaviana de; Marcondes, Laís Passos; Saad, Paulo César Balade (Universidade do Estado do Rio Janeiro, 2014)
INTRODUCTION:The longevity of the population has brought about chronic nd degenerative diseases, such as Alzheimer's disease. This disease emphasizes the physiological changes of aging, altering a person's ability to care for itself, producing great dependence.OBJECTIVE:To compare the functional capacity of institutionalized elderly people with and without Alzheimer's disease.METHODS:Cross-sectional study involving 201 elderly residents in four long-stay public institutions, divided into experimental group with 20 elderly patients with Alzheimer's disease, and control group with 181 subjects without the disease. We obtained demographic data and participants underwent functional evaluation by Barthel index.RESULTS:The majority of residents were female in both groups; the experimental group had higher age (p=0.002), shorter time to institutionalization (p=0.01) and were dependent (p=0.01), compared with subjects without the disease.CONCLUSION:The elderly institutionalized patients with Alzheimer's disease have lower functional capacity than elderly residents without the disease.

INTRODUÇÃO: A longevidade da população trouxe à tona doenças de natureza crônica e degenerativa, como a doença de Alzheimer. Esta doença acentua as alterações fisiológicas do envelhecimento, alterando a capacidade da pessoa para cuidar de si mesma, produzindo grande dependência. OBJETIVO: Comparar a capacidade funcional de idosos institucionalizados com e sem a doença de Alzheimer. METODOLOGIA: Estudo transversal do qual participaram 201 idosos residentes em quatro instituições públicas de longa permanência para idosos, divididos em grupo experimental com 20 idosos com doença de Alzheimer e grupo controle com 181 idosos sem a doença. Foram obtidos os dados sociodemográficos, e os idosos foram submetidos a avaliação funcional pelo índice de Barthel. RESULTADOS: A maioria dos residentes era do gênero feminino em ambos os grupos; o grupo experimental apresentou maior idade (p=0,002), menor tempo de institucionalização (p=0,01) e dependência (p=0,01) em comparação aos idosos sem a doença. CONCLUSÃO: Os idosos institucionalizados com doença de Alzheimer apresentam menor capacidade funcional que os idosos sem a doença.
Functional capacity of institutionalized elderly with and without Alzheimer's disease
Keywords: Idoso; Instituição de Longa Permanência para Idosos; Saúde do Idoso; Doença de Alzheimer; Elderly; Homes for the Aged; Health of the Elderly; Alzheimer Disease